Ephaptic crosstalk in Painful Diabetic Neuropathy: an electrodiagnostic study. - Ahmad Asmedi; Samekto Wibowo; Lucas Meliala (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Painful Diabetic Neuropathy (PDN) is a common complication of diabetes mellitus(DM) which significantly causes pain and distress in patients. Release of factors fromdegenerating fibers activating adjacent fibers to produce ephaptic crosstalk have beenproposed as one of the pain mechanism in PDN. Here we aim to detect ephaptic crosstalkbetween small fibers and large fibers in PDN subjects by comparing the electrodiagnosticresult of patients with PDN and patients without PDN.This study used cohort prospective design. Patients with type 2 DM or impairedglucose tolerance (IGT) without PDN from several health facilities in Yogyakarta werefollowed for 12 months for the occurrence of PDN. Demographic, clinical, laboratory andelectrodiagnostic data from all patients were collected and analyzed.One hundred and forty-one subjects (58 men, 83 women) with an average age of 51years (range, 40–61 years), were enrolled in this study. After 48 weeks of observation,12 subjects were found to have PDN. The differences of distal latency between PDNand non-PDN group were significant when measured in median sensory nerve (4.47 ms±2.43 versus 3.39 ms ±1.79, p = 0.002), tibial motor nerve (6.96 ms ±3.07 versus5.90 ms ±2.17, p = 0.041), and sural sensory nerve (6.02 ms ±3.56 versus 3.55ms ±2.90, p <0.001). Among all parameters measured in this study, the H-reflex hadhigher abnormality persentage compared to other electrodiagnostic variable (H latency =30%, H amplitude = 71%, H/M Ratio = 88%, and H-M IPL = 15%).Our result shows that small fiber neuropathy in PDN can be detected by electrodiagnosticstudy which measures large fibers function. This indicates that ephaptic crosstalkbetween small fiber and large fiber happens in PDN.